'Promoted widely but not valued': Teachers' perceptions of team teaching as a form of professional development in post-primary schools in Ireland. Issue 4 (8th August 2022) - Walsh, Thomas
ABSTRACT: Team teaching as a concept and approach has long been advocated at a policy level both internationally and in Ireland. However, there is very little focussed research on the use of team teaching as an approach in post-primary schools in Ireland or on its potential as a medium of teacher professional development. This article presents the findings of a two-year collaboration between the Department of Education, Maynooth University and the Professional Development Service for Teachers (PDST) to support student teachers and qualified teachers to engage in team teaching. It reports on the context for the collaboration and the educational policy landscape relating to team teaching in Ireland. The main focus of this paper is to report the perceptions of experienced teachers about the potentialities of team teaching as a form of professional development. The findings highlight the fragmented and tenuous way in which team teaching exists in many schools, with one teacher asserting that it is 'promoted widely but not valued'. Despite challenges, the data affirm a very strong appetite among post-primary teachers in Ireland for increased support to use team teaching as an approach that they report to be a valuable medium of professional development.